Essentials of medical surgical nursing - Basavanthappa, BT Professor and principal (Retired) Government College of Nursing, Bengaluru Karnataka, India (Nueva Deli, India : Jaypee Brothers Medical Publishers (P) LTD, 2011)
The book is based on course and curricula of nursing sutdents. It is designed to provide nursing students with the khowledge and skill they need to become complement, think critically and possess the sensitivity to become caring nurses.
Contenido 1. Introduction to medical surgical nursing 2. Management of common signs and symptoms 3. Nursing management of respiratory problems 4. Nursing management of digestive disorders 5. Nursing management of cardiovascular disorders 6.Nursing management of hematological disorders and other 14 chapters
Incluye Contenido
Incluye Indice
Keywords: NURSING; ENFERMERÍA